Persepsi dan Perilaku Mahasiswa Keperawatan tentang Integritas Akademik - Lisa Musharyanti; Gandes Retno Rahayu; Yayi Suryo Prabandari (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2012)
Background: Besides knowledge and clinical skills, nursing students should have professional behavior as an essential component of competences as a side of knowledge and clinical skills. One aspect of professionalism is academic integrity. Lecturer should know about students’ perception of academic integrity and behavior, to make a good way to detect and prevent the deviant behavior. The objective of this study is to describe nursing students’ perception and behavior on academic integrity.Method: Survey was conducted in a nursing school in Yogyakarta. The subject were 230 nursing students who were taken by proportionate stratified random sampling. The data were analyzed with descriptive analysis.Results: There were many deviant or unacceptable behaviors which were not considered as an academic misconduct (by 5.2%-61.3% students). Peer students’ percentage who had done an academic misconduct with 10 of the highest percentage was 50%-82.2% and the behavior ever done by students was 28.7%-68.7%. The intention to do the behavior in the future was 3-38.7%.Conclusion: Perceptions of nursing students on academic integrity varied widely. Many of the actual behaviors were not considered as academic misconduct. Nursing students had different opinions about the behavior that violated academic integrity. Students’ perceptions about the behavior and the behavior of a peer friend were in accordance with the students’ own behavior. Therefore, there is a need for a shared perception between institutions and students about behaviors that violate academic integrity.